Empirical Analysis of the Wagner Hypothesis of Government Expenditure Growth in Kenya: ARDL Modelling Approach - Kibara Manyeki, John; Kotosz, Balázs (Theory, Methodology, Practice – Review of Business and Management, 2017)
Government spending patterns in developing countries have changed dramatically over the last several decades. This paper aims at analysing the relation between government expenditures (GE) and economic growth in Kenya. The study focuses on testing the various versions of Wagner’s hypothesis using Kenya, data from 1967-2012 by an Autoregressive-Distributed Lag (ARDL) model. Overall, we conclude that the Musgrave version is best suited for Kenyan cases since it produced significant long-run and short-run results that were accepted by diagnosis and stability tests. The results rejected Wagner’s hypothesis in Kenya.